Methionine-specific nonreversible bioconjugation: Advancing precision protein modification - Shirui Wang; Zhenguo Zhang; Raymond Tio; Bohan Li; Joycelyn Yi Xin Khoo; Teck-Peng Loh (Proceedings of the National Academy of Sciences, 2026)
We present a methionine-selective, nonreversible bioconjugation strategy that employs activated allylic bromides under mild, aqueous reaction conditions compatible with various peptides and proteins. Compared with conventional allylic bromides, our method improves conjugate stability and suppresses nonspecific reactivity under the examined reaction conditions. This method enables methionine-preferred labeling of peptides and proteins, and provides proof-of-concept applications in covalent inhibitor design and protein functionalization. As a complementary addition to existing methionine bioconjugation strategies, this chemistry expands the toolkit available for protein modification and chemical biology research.